21st Century Retro: Mad Men and 1960s America in film and television - Baruah, Debarchana (American culture studies, 2021)
Frontmatter -- Contents -- Acknowledgements -- Introduction -- Part I -- Chapter 1: Retro -- Chapter 2: History in Retros -- Part II -- Chapter 3: Television Memories and Intertextualities in Mad Men -- Chapter 4: Mad Men and its Paratexts -- Part III -- Chapter 5: The Mad Men Network -- Conclusion -- List of Mad Men Episodes Cited -- Works Cited
Keywords: Hochschulschrift; Mad Men; Geschichte 1960-1970; USA